The isolation, characterisation and investigation into the In vitro behaviour of human ocular vascular endothelial cells - Browning, Andrew C. (2013)
Intraocular angiogenesis is associated with a number of common, blinding conditions including wet age-related macular degeneration, proliferative diabetic retinopathy, retinopathy of prematurity and rubeotic glaucoma. The pathogenesis of these disorders is centered on choroidal, retinal and iris microvascular endothelial cells (ECs) respectively. When studying these conditions, workers have applied conclusions from in vitro studies of human umbilical vein EC (HUVEC) and microvascular endothelial cells, derived from different species or organs. However it is now widely accepted that endothelial cells are very heterogeneous and .extrapolation of results from these cells may not provide reliable data applicable to human eye disease. I have successfully isolated and cultured matched human retinal, choroidal and iris endothelial cells (and sourced HUVECs) and have examined their gene expression profiles. I found wide differences in gene expression between HUVEC and ocular ECs and in addition, between matched human retinal and choroidal endothelial cells. Taken together, these results suggest that HUVECs are not suitable surrogates for studying human ocular disease and secondly. It has implications for our understanding and treatment of retinal and choroidal vascular diseases. To further define the heterogeneity of endothelial cells within a vascular bed, I developed a technique for the isolation of human inner choroidal ECs. After the cells were characterized by surface marker expression, the response of these unique cells to various growth factors was defined and gene expression microarray analysis was performed and compared with matching outer choroidal ECs. This demonstrated differences in genes involved in fenestration formation and growth factor expression. These findings may have implications for our understanding of macular diseases. Overall, this body of work provides an insight into endothelial cell heterogeneity within the eye and may provide clues as to the reasons for ocular vascular bed disease susceptibility and helps identify potential future selective anti-angiogenic treatments.